Groundnut, maize and cassava yields in mixedfood crop fields after calliandra tree fallow in southern Cameroon - Nolte, C.; Tiki-Manga, T.; Badjel-Badjel, S.; Gockowski, J.; Hauser, S. (Cambridge University Press, 2005)
Shortened fallow periods lead to a decline in crop yields in traditional mixed-food crop fields in southern Cameroon. Farmers use no inputs such as fertilizers for crop production in these field types. Planted fallows with adapted tree species might sustain or increase crop production under those conditions, as found in other parts of Africa. Two-year-old calliandra tree fallows, with trees planted in alleys, clusters, equidistantly or around plot borders, were compared with two- and four to five-year-old natural fallows for their effect on groundnut, maize and cassava yields on eighteen farmer fields in southern Cameroon. Trial fields covered a wide range of soil and environmental conditions. The tree fallows had no significant effects on the yields of maize and cassava with the exception of the border planting, in which trees were not rigorously pruned back prior to cropping. Here, cassava tuber yields were reduced. Cassava tuber yields declined generally with decreasing planting distance to trees. The yield of groundnut, the most important crop in this field type, was adversely affected. However, maize grain yields were positively related to biomass produced by calliandra trees, notably on soils with pH over about 5.3. The data indicated that yields of all crops could be increased with higher plant densities, irrespective of fallow type. The tree fallows, with the exception of border planting, showed less adaptability than four to five-year-old natural fallows to sites with low crop yields, whereas no difference compared with two-year-old natural fallows was found.